Psychological Characteristics Of Developing Professional Motivation In Students Of The Psychology Education Program - Feruza Nosirjonovna Boboyeva (Researchparks Publishing, 2026)
This study examines the psychological characteristics of developing professional motivation in students enrolled in the psychology education program. Professional motivation is a key factor influencing students’ academic success, career orientation, and personal growth. The research analyzes both internal factors, such as personal interests, cognitive abilities, and self-efficacy, and external factors, including social environment, teacher support, and educational strategies. The study emphasizes the role of psychological mechanisms, such as goal-setting, self-regulation, and intrinsic motivation, in fostering a sustainable professional orientation. Results indicate that a combination of individual and environmental influences is crucial for enhancing motivation, increasing engagement, and promoting successful professional development. The findings are applicable to educational practice and curriculum design, providing insights for teachers, psychologists, and program developers to create effective motivational strategies tailored to psychology students.